A matemacia em projetos de modelagem matemática : contribuições para licenciandos em Matemática - Petry, Polyanna Possani da Costa (2023)
This investigation aims to understand how the acts of communication are involved in Mathematical Modeling Projects, and how they contribute for the development of mathemacy of Mathematics undergraduate, in the context of an extracurricular Training Activity. Therefore, we carry out qualitative research in the context of a training activity, developed remotely with synchronous meetings and asynchronous activities, with students of the degree program in Mathematics at the State University of Mato Grosso – UNEMAT (Sinop campus), from March 17th to May 17th, 2021, using technology resources such as Google Meet, Google Classroom and WhatsApp. The research had a total of eight participants, who, organized in pairs, developed the following Mathematical Modeling Projects: the variation in purchasing power in relation to the minimum wage between the years 2000 to 2021; does trade closure work? A basic analysis of the efficiency of decrees that close trade as a means of reducing the spread of the Coronavirus; return to classes in hybrid mode at a municipal school in the municipality of Sinop in view of the pandemic; fake news.The theoretical contribution of this work focuses on Critical Mathematics Education concepts discussed by Ole Skovsmose, specifically on the idea of mathemacy and the concepts related to it, and Mathematical Modeling in Mathematics Education in the perspective defended by Araújo (2002) and Barbosa (2001a). In data production, we have had the help of the following procedures and instruments: observation of undergraduate students in synchronous meetings, logbooks, meetings recording and semi-structured interviews. The data generated were analyzed by Dialogical Discourse Analysis, based on Bakhtinian assumptions, having as categories: mathematical knowledge, technological knowledge, reflection on Mathematics, reflection with Mathematics and acts of communication. As a result, we have that the Mathematical Modeling Projects contributed to the development of the mathemacy of Mathematics undergraduates in the context of an extracurricular Training Activity, through a learning environment that, through Mathematics, invited the undergraduate students to question and investigate non-mathematical situations with reference in the reality chosen by them. Thus, based on the issues of Critical Mathematics Education, throughout the development process of the Mathematical Modeling Projects, the acts of communication that make up the Investigative Cooperation Model were identified as drivers of the development of the Mathematical Modeling Projects, further indicating that the Mathematical Modeling Projects were developed in a process of investigative cooperation.